Ice and Debris Passage for Innovative Lock Designs - Tuthill, Andrew M. (2003)
Physical and numerical models were used to assess ice and debris passage at navigation locks focusing on key factors such as the configuration of the upper approach, the design of the lock filling and emptying system and the location and design of culvert intakes and outlets. Unconventional ice passage techniques such as manifolds in the miter gates were also evaluated. Physical model results were compared to field observations and a parallel series of tests using the DynaRICE ice-hydraulic numerical model. Ice processes modeled included upper approach ice accumulation during lock filling, drawing ice into the lock chamber and flushing ice out of the lock. Initial ice thickness was found to be the most important parameter affecting ice passage. Physical and numerical model results compared reasonably well proving DynaRICE to be a useful tool for assessing ice passage for new lock designs. The original document contains color images.